The best American magazine writing 2002 - American Society of Magazine Editors (New York : Perennial, 2002)
Presents nineteen magazine articles selected as winners or finalists in the annual National Magazine Award competition, covering the categories of feature writing, reporting, essays, columns and commentary, leisure interests, reviews and criticism, profile writing, public interest, and fiction.
Library Journal.
Publisher's Weekly.
3.3.
3.3
Adult
Keywords: American prose literature -- 20th century; American prose literature